Zwrot . informator wewnętrzny Niezależnego Samorządnego Związku Zawodowego "Solidarność" przy SGPiS, no. 11, 1981 - "Solidarność" SGPiS, [selected and ed. by Piotr Brażewicz et al.] (NSZZ "Solidarność" przy SGPiS, 1981)
Creation and circulation: After introduction of the Martial Law publication suspended in 1982-1988. Republished in 1989